Food Insecurity has Increased around the World. Issue 2 (March 2023) - Callister, Lynn Clark
Abstract : Food insecurity has increased around the world. Our global health and nursing expert, Dr. Callister, reviews several recent international reports of food insecurity and world hunger and highlights efforts by multiple organizations to help with this crisis that affects millions of families, women, and children.